Challenges in the Treatment of Glioblastoma by Chimeric Antigen Receptor T-Cell Immunotherapy and Possible Solutions - Zhang, Peng; Zhang, Yang; Ji, Nan (Frontiers in Immunology, 2022)
Glioblastoma (GBM), one of the most lethal brain cancers in adults, accounts for 48.6% of all malignant primary CNS tumors diagnosed each year. The 5-year survival rate of GBM patients remains less than 10% even after they receive the standard-of-care treatment, including maximal safe resection, adjuvant radiation and chemotherapy with temozolomide. Therefore, new therapeutic modalities are urgently needed for this deadly cancer. The last decade has witnessed great advances in chimeric antigen receptor T (CAR-T) cell immunotherapy for the treatment of hematological malignancies. Up to now, the US FDA has approved six CAR-T cell products in treating hematopoietic cancers including B-cell acute lymphoblastic leukaemia, lymphoma and multiple myeloma. Meanwhile, the number of clinical trials on CAR-T cell has increased significantly, with more than 80% from China and the United States. With its achievements in liquid cancers, clinical efficacy of CAR-T cell therapy has also been explored on a variety of solid malignancies, that include GBMs. However, attempts to expand CAR-T cell immunotherapy in GBMs have not yet presented promising results as in hematopoietic malignancies. Like other solid tumors, CAR-T cell therapies against GBM still face several main challenges, those are tumor heterogeneity, tumor immunosuppressive microenvironment and CAR-T cell persistence. Hence, developing strategies to overcome these challenges will be necessary for accelerating the transition of CAR-T cell immunotherapy against GBMs from bench to bedside.